Identification of a Ligand Binding Pocket in LdtR from Liberibacter asiaticus - Fernando A Pagliai; Claudio Fabricio Gonzalez; Graciela L Lorca (Frontiers in Microbiology, 2015)
LdtR is a transcriptional activator involved in the regulation of a putative L,D transpeptidase in Liberibacter asiaticus, an unculturable pathogen and one of the causative agents of Huanglongbing disease. Using small molecule screens we identified benzbromarone as an inhibitor of LdtR activity, which was confirmed using in vivo and in vitro assays. Based on these previous results, the objective of this work was to identify the LdtR ligand binding pocket and characterize its interactions with benzbromarone. A structural model of LdtR was constructed and the molecular interactions with the ligand were predicted using the SwissDock interface. Using site-directed mutagenesis, these residues were changed to alanine. Electrophoretic mobility shift assays, thermal denaturation, isothermal titration calorimetry experiments, and in vivo assays were used to identify residues T43, L61, and F64 in the Benz1 pocket of LdtR as the amino acids most likely involved in the binding to benzbromarone. These results provide new information on the binding mechanism of LdtR to a modulatory molecule and provide a blue print for the design of therapeutics for other members of the MarR family of transcriptional regulators involved in pathogenicity.